Effect of holes system designing for low energy stove using coffee husk bio-pellet as solid fuel - Sisbudi Harsono, Soni; Prayogo, B; ,, Tasliman; Mel, Maizirwan; Ridha, Fabrobi (Penerbit Akademia Baru, 2018)
Bio-pellet is an important fuel for sustainable energy in future and a potential renewable energy substitute for rural areas, East Java of Indonesia in particular. One of the candidates for solid fuel is coffee husk pellets, it is a bio-product produced from coffee production waste. In this research, focus is on hole design of stove that could be used for generating energy from coffee husk pellet generally used as feedstock. This designed device also could be used as an alternative for gas-powered stoves. The variations in stove designs were proposed and has been modified as required. It is conducted in the stove’s combustion cylinder. A particular stove (OS1) was used as control and other stoves were tested to measure the heat, thermal efficiency and emissions. The heat was produced at 316,880 kJ, 310,601 kJ, 308,229 kJ, and 306,833 kJ for stoves of 40, 20, 10 hole variation and OS1, respectively. Thermal efficiency for #OTHER stove were 16.47%, 16.39% for 10 holes, 15.96% for 20 holes of and 15.38% for 40 holes, respectively. The emissions results obtained were 333ppm for OS1, 298 ppm for 10 holes, 289 ppm for 20 holes, and 273 ppm for 40 holes of stove, respectively. As a conclusion, the stove with 40 holes variation, is selected as the most desired for this type of pellet stove.